2019
DOI: 10.14238/pi31.9-10.1991.273-80
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopneumonia with measles in Infants and Children at the Department of Child Health School of Medicine, University of North Sumatera/ Dr. Pirngadi Hospital Medan (January 1985 - December 1989)

Abstract: A retrospective study was done on patients with bronchopneumonia hospitalized at the Dr. Pirngadi Hospital Medan/School of Medicine, University of North Sumatera; during January 1985 through December 1989. The purpose of this study is to assess the morbidity and mortality of bronchopneumonia with measles and the nutritional status of the patients. Out of the 14.082 patients admitted, 1310 children suffered from bronchopneumonia (10.7%). Ninety nine of them were also with measles (7.6%). Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Serious risk implication of incomplete immunization status is proven for ALRI by several studies. 7,10,11,14,19,28,30,[48][49][50] The evidence gathered by present study is by and large consistent with understanding on risk factors for ALRI in less than 5 year children. There is overt variance however, in respect of quantitative contribution of risk factors in this study and other reports.…”
Section: Discussionsupporting
confidence: 86%
“…Serious risk implication of incomplete immunization status is proven for ALRI by several studies. 7,10,11,14,19,28,30,[48][49][50] The evidence gathered by present study is by and large consistent with understanding on risk factors for ALRI in less than 5 year children. There is overt variance however, in respect of quantitative contribution of risk factors in this study and other reports.…”
Section: Discussionsupporting
confidence: 86%
“…While this association has been consistently documented for diarrheal and acute respiratory infections, the evidence for deaths due to measles has been less consistent across studies [3]. Most community-based studies have found no evidence for an association between measles mortality and nutritional status [4], [5], while many hospital-based studies [6], [7] have shown an association [2], [3]. However, the majority of these studies, both hospital and community-based, are unable to examine the association of measles mortality with nutritional status prior to infection with measles.…”
Section: Introductionmentioning
confidence: 99%